Integrasi teknologi AI dalam Pembelajaran adaptif untuk Meningkatkan Keterampilan Abad 21 di Sekolah Dasar - Riska, Nina; Rosmilawati, Ila; Juansah, Dase Erwin (LPPM Universitas Bina Bangsa, 2025)
This research aims to examine the contribution of artificial intelligence (AI) technology in the application of adaptive learning and evaluate its influence on the development of 21st century skills in elementary school students. The approach used is a literature study using the systematic literature review (SLR) method on various relevant scientific publications. The results of the analysis show that the application of AI in adaptive learning is able to facilitate the personalization of the learning process by identifying students' learning needs, providing direct feedback, and adjusting learning materials to each individual's abilities. In addition, AI also contributes to strengthening six main competencies for the 21st century, namely critical thinking, cooperative skills, communication, creativity, digital literacy, and media literacy. AI-based learning also encourages increased motivation and student engagement in an interactive and contextual learning process. However, there are obstacles to implementation, such as lack of technological infrastructure, low digital literacy of educators, and limited curriculum policy support. Therefore, efforts are needed to strengthen infrastructure, improve teacher competence, and develop education policies that support comprehensive AI integration. These findings reinforce that AI has a strategic role in supporting the transformation of basic education in the current digital era.